2011
DOI: 10.1096/fj.11-193979
|View full text |Cite
|
Sign up to set email alerts
|

SirT1 catalytic activity is required for male fertility and metabolic homeostasis in mice

Abstract: The protein encoded by the sirt1 gene is an enzyme, SirT1, that couples the hydrolysis of NAD(+) to the deacetylation of acetyl-lysine residues in substrate proteins. Mutations of the sirt1 gene that fail to encode protein have been introduced into the mouse germ line, and the animals homozygous for these null mutations have various physiological abnormalities. To determine which of the characteristics of these sirt1(-/-) mice are a consequence of the absence of the catalytic activity of the SirT1 protein, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
67
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(71 citation statements)
references
References 55 publications
3
67
1
Order By: Relevance
“…4c, e). NAD + is a key factor for the deacetylation activity of the mitochondrial regulator SIRT1 and this protein may play a crucial role in male fertility3334. Since NAD + consumption by hyperPARylation may impair SIRT1 activity33, we further asked whether DEHP treatment could also reduce SIRT1 activity and cause mitochondrial malfunction.…”
Section: Resultsmentioning
confidence: 99%
“…4c, e). NAD + is a key factor for the deacetylation activity of the mitochondrial regulator SIRT1 and this protein may play a crucial role in male fertility3334. Since NAD + consumption by hyperPARylation may impair SIRT1 activity33, we further asked whether DEHP treatment could also reduce SIRT1 activity and cause mitochondrial malfunction.…”
Section: Resultsmentioning
confidence: 99%
“…There is increasing evidence that SirT1 may have other activities aside from HDAC activity. As an example, Pfister et al [36] have shown that overexpression of different SirT1 mutants with catalytic-site mutations may still be neuroprotective while Seifert et al [37] showed that SirT1 may have both HDAC-dependent and -independent roles. Finally, HDAC4, highly relevant for HD, is known to have at least two enzymatic activities (HDAC and SUMO ligase activities).…”
Section: Sirt1mentioning
confidence: 99%
“…First, to determine whether the effect of Sirt1 on Aire-driven gene expression was dependent on its catalytic activity, we used a well-established transgenic mouse model in which the wild-type Sirt1 allele is replaced with a mutated Sirt1 allele that encodes a catalytically inactive Sirt1 protein (Sirt1 H355Y ) 29 . Indeed, quantitative PCR analysis showed significantly lower expression of Aire-dependent genes in mTECs sorted from Sirt1 H355Y mice than in those from Sirt1 +/+ mice (Fig.…”
Section: Sirt1 Interacts With Aire and Induces Its Deacetylationmentioning
confidence: 99%
“…B6.Sirt1 fl/fl mice (Jackson Laboratories) were crossed with B6.Foxn1-Cre mice (obtained from D. Graf with the consent of N. Manley) for the generation of Sirt1 fl/fl Foxn1-Cre mice. Sirt1 −/− and Sirt1 H355Y mice 28,29,34 were maintained on a mixed 129sv/ICR genetic background. B6.Aire-GFP reporter (Adig) mice and the NOD.Aire −/− mice were provided by M. Anderson and by D. Mathis and C. Benoist, respectively.…”
Section: Author Contributionsmentioning
confidence: 99%